2016
DOI: 10.4172/2325-9795.1000238
|View full text |Cite
|
Sign up to set email alerts
|

Male and Female Differences in Health Benefits Derived from Physical Activity: Implications for Exercise Prescription

Abstract: Males are consistently reported as more physically active than females regardless of age or measure. Often, this difference results in females identified as under active and at risk of longterm poor health outcomes. In this paper a different perspective drawing on evidence from many sources is offered. Males and females gain different health benefits according to the level, mode and intensity of the physical activity. Some potential ramifications of these gender differences in health benefits are evident in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 63 publications
3
64
1
3
Order By: Relevance
“…Moreover, the differences in jobs performed by men and women may bring along a different set of (socioeconomic and associated lifestyle) factors, possibly explaining the gender differences found in our study. Finally, as it has been shown that men and women respond differently to cardiovascular risk factors,78 including PA,33 a different response to occupational PA by gender is possible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the differences in jobs performed by men and women may bring along a different set of (socioeconomic and associated lifestyle) factors, possibly explaining the gender differences found in our study. Finally, as it has been shown that men and women respond differently to cardiovascular risk factors,78 including PA,33 a different response to occupational PA by gender is possible.…”
Section: Discussionmentioning
confidence: 99%
“…HRs with 95% CI were reported, depicting individual study and pooled associations of high (compared with low) level occupational PA with all-cause mortality in forest plots. Due to apparent gender differences in occupational PA levels32 and physiological responses to PA,33 analyses were stratified by gender (as stipulated in our a priori registered protocol26). Funnel plots were generated to assess publication bias 34.…”
Section: Methodsmentioning
confidence: 99%
“…O estímulo promotor de marcha e de ciclismo para as mulheres pode ser uma estratégia de sucesso para diminuir as diferenças de prevalência de AF entre os sexos, desfavorável a favor das mulheres. 9,10 . A inatividade física feminina é uma preocupação que, embora seja apenas uma peça em um quadro complexo, pode estar contribuindo para o aumento das condições adversas à saúde das mulheres.…”
Section: Discussionunclassified
“…There is some evidence that females receive health benefits from lighter physical activity and do not require the same intensity and amount of physical activity compared to males (Hands, Parker, Larkin, Cantell, & Rose, 2016), and are often less motivated to participate (Labbrozzi et al, 2013). Other studies have also suggested that perceived competence plays a role in engagement of physical activity (Ferrer-Caja & Weiss, 2000;Sollerhed et al, 2008), therefore girls may choose to participate less due to feelings of poor competency in physical activity tasks and place less value on sports participation (Fredricks & Eccles, 2005;Slater & Tiggemann, 2011).…”
Section: Discussionmentioning
confidence: 99%